Engineering design - Dieter, George E.; Schmidt, Linda C. (McGraw-Hill, 2021)
Engineering design continues its tradition of presenting an in-depth foundation of the engineering design process. In addition, it emphasizes material selection and design for manufacture, with the overarching goal of design quality. The teaching of the engineering design process has been made more coordinated by reorganizing some of the chapters. The text is intended for use in either a junior or senior engineering design course as well as a graduate-level course on the design process.